Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-021-03913-5
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and clearance of anal high-risk Human Papillomavirus infection and their risk factors in men who have sex with men living with HIV

Abstract: HIV-infected men who have sex with men (MSM) display the highest prevalence of anal infection by high-risk Human Papillomaviruses (hrHPVs) and incidence of anal carcinoma. Anal specimens were genotyped by the Linear Array. Incidence and clearance of anal infection by hrHPVs, hrHPVs other than HPV16, low-risk HPVs, and four individual types (6,11,16,18) were estimated using a two-state Markov model. Determinants for incidence and clearance were assessed by logistic regression. Overall, 204 individuals were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Most studies analyzing the impact of cART on HPV infection reported beneficial effect [ 19 , 20 , 33 – 35 ]. A meta-analysis concluded that cART is associated with decreased prevalence of anal HR-HPV infection in HIV population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies analyzing the impact of cART on HPV infection reported beneficial effect [ 19 , 20 , 33 – 35 ]. A meta-analysis concluded that cART is associated with decreased prevalence of anal HR-HPV infection in HIV population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis concluded that cART is associated with decreased prevalence of anal HR-HPV infection in HIV population [ 19 ]. A prospective study reported that cART reduces the risk of acquiring anal HR-HPV infection in HIV positive men who have sex with men (MSM) [ 20 ]. However, negative or null associations were also reported [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are very few longitudinal cohort studies examining the association between incident and prevalent HPV and the risk of anal hrHPV infection over time, particularly in sexual and gender minority populations. Among the identified literature on anal HPV infection among SMM, most studies focus exclusively on HIV-positive SMM ( Donà et al, 2022 ; Fuchs et al, 2016 ; González et al., 2013 ), few report on risk factors beyond HIV ( Donà et al, 2022 ; González et al, 2013 ; Yunihastuti et al, 2020 ), and all are conducted outside the United States ( Brown et al, 2018 ; Donà et al, 2022 ; Fuchs et al, 2016 ; González et al, 2013 ; Mooij et al, 2016 ; van Aar et al, 2013 ; Yunihastuti et al, 2020 ; Zou et al, 2015 ). Only one study included SMM residing in the United States, though they comprised less than 3% of the sample of heterosexual and sexual minority men across North and South America ( Nyitray, Carvalho da Silva, Baggio, Smith, et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anal carcinoma is a malignant proliferative disease associated with anal abnormalities ( 1 ). With strong sex bias (females have higher mortality), more than 1000 people die of anal carcinoma per year in the United States ( 2 , 3 ). The risk factors for anal carcinoma include aging, sex (more than two-thirds of patients are women), smoking, and most importantly human papilloma virus (HPV) infection ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%